The Impact of Sampling and Measurement on the Prevalence of Self-Reported Pain in Canada - Elizabeth G Van Den Kerkhof; Wilma M Hopman; Tanveer E Towheed; Tassos P Anastassiades; David H Goldstein (Pain Research and Management)
BACKGROUND: Pain is an important public health problem in Canada. International estimates of general population pain prevalence range from 2% to 46%.